Selection of Furniture Raw Material Suppliers using Fuzzy Analytical Hierarchy Process - Chairul Diah Utami; Ahmad Kholid Alghofari; Hafidh Munawir; Much Djunaidi (Department Industrial Engineering, University of Muhammadiyah Malang, 2019)
The raw material is an essential aspect of ensuring smooth production. The selection of raw material suppliers needs to be done to sustain the company's production and development. Wisarka company is an export-oriented furniture company. It uses water hyacinth (Eichhornia crassipes) as the primary raw material. The company is required to maintain and improve performance. The company needs to select the right supplier. This study uses the Multi-Criteria Decision Making (MCDM) the Fuzzy Analytical Hierarchy Process (FAHP) method. It was used for selecting suppliers with criteria like price, quality, flexibility, delivery, warranty, and service. The result of the study show FAHP effective in selecting suppliers.